Molecular dynamics simulations of aqueous glycine solutions. Issue 47 (22nd November 2017) - Bushuev, Yuriy G.; Davletbaeva, Svetlana V.; Koifman, Oscar I.
Abstract : Pre-nucleation clusters of glycine are strongly hydrated dynamic solutes, which change size and shape within hundreds of picoseconds. Abstract : Simulations of glycine aqueous solutions have been carried out to study the effect of increasing solute concentration on the aggregation of glycine zwitterions. AMBER force field coupled with three atomic charge sets was employed for the simulations of the aqueous solutions. The number of glycine monomers in solutions rapidly decreases with increase in concentration. The properties of the glycine clusters in the solutions were studied. It was shown that the clusters are strongly hydrated entities with a liquid-like character. The residence lifetimes of water and glycine from the first solvation shell of glycine molecules were calculated. The lifetime values show that the clusters are highly dynamic solutes that change configuration within hundreds of picoseconds. We observed long-living pairs of glycine molecules, which move together in the solutions for ca. 1 ns. The effect of the electric-field-induced orientation of the highly polar glycine molecules in the clusters was studied. A preferential parallel arrangement of the molecules was observed as the distinctive feature of the γ-polymorph, which was crystallized from the solutions in a static electric field.